2015
DOI: 10.1051/epjconf/201510200005
|View full text |Cite
|
Sign up to set email alerts
|

Dust Opacities

Abstract: Abstract. Dust particles are the dominant source of opacity at (almost) all wavelengths and in (almost) all regions of protoplanetary disks. By this they govern the transport of energy through the disk and thus the thermal structure. Furthermore, their spectral properties determine the low resolution spectral signature observed at infrared wavelengths. The infrared resonances that can be observed using low resolution infrared spectroscopy can be used to identify the composition and size distribution of the dus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…A distribution of these particles with different fractions of volume being the vacuum core are then averaged over. This represents well the distributions of irregularly shaped particles for protoplanetary disks, both in the Rayleigh regime and for larger particles (Min et al 2003(Min et al , 2008Min 2015), and has now also been implemented in atmospheric models ATRES (Stolker et al 2017), PetitCODE (Mollière et al 2015(Mollière et al , 2017, ARCiS (Ormel & Min 2019;Chubb et al 2020) and also in retrievals PetitRADTRANS (Mollière et al 2019).…”
Section: Observational Implicationsmentioning
confidence: 86%
“…A distribution of these particles with different fractions of volume being the vacuum core are then averaged over. This represents well the distributions of irregularly shaped particles for protoplanetary disks, both in the Rayleigh regime and for larger particles (Min et al 2003(Min et al , 2008Min 2015), and has now also been implemented in atmospheric models ATRES (Stolker et al 2017), PetitCODE (Mollière et al 2015(Mollière et al , 2017, ARCiS (Ormel & Min 2019;Chubb et al 2020) and also in retrievals PetitRADTRANS (Mollière et al 2019).…”
Section: Observational Implicationsmentioning
confidence: 86%
“…For the same parameters (c i = c j ), the matrix (m) i j coincides with the identity matrix. Equations (17) imply that z sca = −A 11 A −1 31 z in , and as a result we obtain the so-called " spheroidal" (since expansions in spheroidal functions are used) T -matrix for the potential p:…”
Section: Solution Of the Axisymmetric Problemmentioning
confidence: 99%
“…The disadvantage of the approach is that the computational problems for spheroids increase rapidly with increasing diffraction parameter, ratio of semiaxes, or refractive index. In particular, in astrophysical applications the first one and sometimes the second one [16,17] are critical, while in microwave experimentsthe third one [18]. In addition to those listed above, to calculate the optical properties of spheroids one can apply universal methods developed for particles of arbitrary shape and structure (see, for example, the review in [19]).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found good agreement between the three distributions considered for the Rayleigh regime (Min et al 2003), and they further found that hollow spheres replicate laboratory experiments of irregularly shaped quartz particles well (Min et al 2005) for larger particles. We used the distribution of hollow spheres because it can be calculated using an extension of the Mie theory and thus yields very fast results (Min 2015).…”
Section: Particle Shapementioning
confidence: 99%